PERMINTAAN WISATA ALAM DI KOTA SEMARANG BAGI KELOMPOK USIA MUDA - Ari Listyowati; E.K.S Harini Muntasib; Rachmad Hermawan (Media Konservasi, 2013)
Researh was done to know  the potential and actual demands of nature-based tourism of young age group (15-24 years old) at Semarang City,  and to determine the factors was influencing to  tourism demand. Result of reseach  was showed that the potential demand of nature-based tourism for young age group at Semarang City about 82.20% of the total number of young age group (241474 individuals).Potential demand of tourism based on tourism objects i.e  mountain (20.144 individuals). beach (14.458 individuals), cave (9.322 individuals), and waterfall (7.458 individuals), Result of research also showed that the  factors which influence the actual demand of tourism were parents occupation, interest foward tourism objects, reason of visit, and time of visit. Reason to visit the tourism area are enjoy the scenery and to find the  fresh air.     Keywords: Nature based tourism, potential demand, actual demand, young age group, Semarang City.